Efficacy of Combination Chemo-Immunotherapy as a First-Line Treatment for Advanced Non-Small-Cell Lung Cancer Patients With HER2 Alterations: A Case Series - Zhao, Shuang; Xian, Xinghong; Tian, Panwen; Li, Weimin; Wang, Ke; Li, Yalun (Frontiers in Oncology, 2021)
Objective: Although the treatment of non-small-cell lung cancer (NSCLC) patients with human epidermal growth factor receptor 2 (HER2) alterations has been studied for years, the overall response rate (ORR) of these patients is still unsatisfactory, and more therapeutic strategies are needed. Little is known about the combination of chemo- and immunotherapy in HER2-altered lung cancer treatment. Materials and Methods: We report five cases of advanced NSCLC with HER2 insertion mutation or amplification treated with immunotherapy combined with chemotherapy as the first-line treatment. The HER2 alteration type, duration of treatment and survival were also analyzed. Results: The five advanced NSCLC patients, three with HER2 mutations and two with HER2 amplifications, received chemo-immunotherapy as the first-line treatment. Their progression-free survival (PFS) ranged from 2-12 months, with a median PFS of 8.0 months. We also observed that patients with HER2 amplification had a longer PFS than those with HER2 insertion mutations among those who received chemo-immunotherapy as the first-line treatment. Conclusions: Chemo-immunotherapy may be a promising first-line treatment option for NSCLC patients with HER2 alterations, especially HER2 amplification. Further clinical trials are required to confirm this therapeutic option.